2017
DOI: 10.1039/c7ra03960c
|View full text |Cite
|
Sign up to set email alerts
|

Role of compensating Li/Fe incorporation in Cu0.945Fe0.055−xLixO: structural, vibrational and magnetic properties

Abstract: Monoclinic single phase Cu0.945Fe0.055−xLixO, with Cu2+ properly substituted by Fe3+ and Li1+, shows enhanced magnetic moment with stronger FM coupling due to Li1+ doping.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 59 publications
(63 reference statements)
0
10
0
Order By: Relevance
“…This beamline operates in the energy range of 4 KeV to 25 KeV. The details and mechanism has been reported earlier [24]. XRD patterns of synthesized CNO0, CNO2, CNO5 and CNO10 (Figure 1(a)) shows (111), (200), (220), (311), (222), (400), (331) and (420) reflection planes of a cubic fluorite structure with space group Fm3m.…”
Section: High Resolution Transmission Electron Microscope (Hrtem) Imamentioning
confidence: 73%
“…This beamline operates in the energy range of 4 KeV to 25 KeV. The details and mechanism has been reported earlier [24]. XRD patterns of synthesized CNO0, CNO2, CNO5 and CNO10 (Figure 1(a)) shows (111), (200), (220), (311), (222), (400), (331) and (420) reflection planes of a cubic fluorite structure with space group Fm3m.…”
Section: High Resolution Transmission Electron Microscope (Hrtem) Imamentioning
confidence: 73%
“…The asymmetric O 1 s peak has been discussed in the literature to arise from three contributions: peaks appearing at approximately 533.83 eV (peak 3 : related to H 2 O adsorbed on the surface of the sample), approximately 531.89 eV (peak 2 : caused by either OH − hydroxyl groups or by chemisorbed molecular oxygen O2) and approximately 530.15 eV (peak 1 , associated with oxygen O 2− in CuO lattice [5,18,19]). We have fitted O 1 s edge with three Gaussian peaks and found that the relative area under peak 1 is increasing with respect to peak 2 and peak 3 with increasing x.…”
Section: Resultsmentioning
confidence: 99%
“…Hence, magnetism should not be attributed to interstitial or externally existing iron clusters. [5,18,19]). We have fitted O 1s edge with three Gaussian peaks and found that the relative area under peak 1 is increasing with respect to peak 2 and peak 3 with increasing x.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The metal oxide NPs are the good physical and chemical properties the NPs. The transition metal Oxide NPs such as MnO, CdO, CuO, ZnO, NiO, and TiO 2 for the best optical, magnetic and electrical properties for the Nanostructures numerous applications in the field of catalyst, sensor, fuel cells, drug delivery, electrochemistry and medicine [6][7][8][9][10][11][12][13]. Among the metal oxides NPs, CuO is considered to be one of the most important p-type semiconductors, Non toxic, low cost, abundant, high electrical conductivity.…”
Section: Introductionmentioning
confidence: 99%